Mining High Utility Itemsets with Regular Occurrence - Komate Amphawan; Philippe Lenca; Anuchit Jitpattanakul; Athasit Surarerks (LPPM ITB, 2016)
High utility itemset mining (HUIM) plays an important role in the data mining community and in a wide range of applications. For example, in retail business it is used for finding sets of sold products that give high profit, low cost, etc. These itemsets can help improve marketing strategies, make promotions/ advertisements, etc. However, since HUIM only considers utility values of items/itemsets, it may not be sufficient to observe product-buying behavior of customers such as information related to